THE SIMPLICITY OF COMPETITIVE REPERTOIRES: AN EMPIRICAL ANALYSIS - Miller, Danny; Chen, Ming‐Jer (Strategic Management Journal, 1996)
This research explores the notion of competitive simplicity: a tendency of some firms to concentrate intensely on just a few central activities. Our focus here is the simplicity inherent in the repertoire of concrete, market-oriented actions used by companies to compete: these actions include product introductions, pricing or advertising decisions, and changes in market scope. The simplicity of a competitive repertoire can be assessed by its range of actions and its degree of concentration on one or a few dominant types of actions. We argue that competitive simplicity is largely a function of organizational and environmental properties that attenuate managerial search or restrict knowledge of competitive alternatives. These properties include good performance, munificent, homogeneous or certain markets, a lack of breadth in competitive experiences, and the complacency that may accompany age and size. Paradoxically, although good past performance may contribute to simplicity, simplicity can hurt subsequent performance, especially during periods of uncertainty and growth. Many of these ideas were borne out in a study of the major carriers of the post-deregulation domestic airline industry.